Measurement of the production of charm jets tagged with D0 mesons in pp collisions at s√=7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Journal of high energy physics, 2019)
The production of charm jets in proton-proton collisions at a center-of-mass energy of s√=7 TeV was measured with the ALICE detector at the CERN Large Hadron Collider. The measurement is based on a data sample corresponding to a total integrated luminosity of 6.23 nb−1, collected using a minimum-bias trigger. Charm jets are identified by the presence of a D0 meson among their constituents. The D0 mesons are reconstructed from their hadronic decay D0 →K−π+. The D0-meson tagged jets are reconstructed using tracks of charged particles (track-based jets) with the anti-kT algorithm in the jet transverse momentum range 5<pchT,jet< 30 GeV/c and pseudorapidity |ηjet| < 0.5. The fraction of charged jets containing a D0-meson increases with pchT,jet from 0.042 ± 0.004 (stat) ± 0.006 (syst) to 0.080 ± 0.009 (stat) ± 0.008 (syst). The distribution of D0-meson tagged jets as a function of the jet momentum fraction carried by the D0 meson in the direction of the jet axis (zch∥) is reported for two ranges of jet transverse momenta, 5<pchT,jet< 15 GeV/c and 15<pchT,jet< 30 GeV/c in the intervals 0.2<zch∥∥<1.0 and 0.4<zch∥∥<1.0, respectively. The data are compared with results from Monte Carlo event generators (PYTHIA 6, PYTHIA 8 and Herwig 7) and with a Next-to-Leading-Order perturbative Quantum Chromodynamics calculation, obtained with the POWHEG method and interfaced with PYTHIA 6 for the generation of the parton shower, fragmentation, hadronisation and underlying event.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel ist die Zahl 0 hochgestellt
*ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband, A. Yuncu [und 999 weitere]
Gesehen am 11.10.2019